2010
DOI: 10.1055/s-0030-1247529
|View full text |Cite
|
Sign up to set email alerts
|

ACEandACTN3Genes and Muscle Phenotypes in Nonagenarians

Abstract: We studied the association of ACE and ACTN3 polymorphisms with skeletal muscle phenotypes (i. e. upper and lower body muscular strength and functional tests) in Spanish nonagenarian subjects [n=41, 33 women, 8 men, age: 90-97 years]. Mean values of the study phenotypes were not significantly different (all P>0.05) between ACE and ACTN3 genotypes. The analyses of the combined effects between genotypes ( ACE DD & ACTN3 RR/RX vs. ACE II/ID & ACTN3 XX) did not yield any significant difference. Our data suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
32
0
2

Year Published

2010
2010
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 21 publications
7
32
0
2
Order By: Relevance
“…With regard to this, in our study, we found no significant association between the ACTN3 R allele + ACE I allele combination (data not shown). As for non-athletic populations, our findings concur with recent data on elderly people showing no association (individually or combined) between power muscle phenotypes and ACE I/D + ACTN3 R577X genotype combinations (Bustamante-Ara et al 2010).…”
Section: Discussionsupporting
confidence: 91%
“…With regard to this, in our study, we found no significant association between the ACTN3 R allele + ACE I allele combination (data not shown). As for non-athletic populations, our findings concur with recent data on elderly people showing no association (individually or combined) between power muscle phenotypes and ACE I/D + ACTN3 R577X genotype combinations (Bustamante-Ara et al 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Other studies, however, have failed to support such findings (Bustamante-Ara et al 2010;Rodriguez-Romo et al 2010). This is mainly because the effect of a single polymorphism on physical function is quite small and therefore difficult to identify (Williams and Folland 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Genetic variation has been used to answer questions as to how adaptations in skeletal muscle and interactions occur. It provides new frameworks to improve physical performance in older people (Ahmetov and Rogozkin 2009;Bustamante-Ara et al 2010;McCauley et al 2010;) being clinically relevant to identifying training response association of different genotypes associated with decreases of strength and function with aging (Garatachea and Lucia 2011). Although previous association studies have suggested a relevant genetic contribution to individual variability in muscle-related phenotypes, published data on specific gene variants are controversial (Bouchard and Rankinen 2001;Garatachea and Lucia 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations